Implementation of guided inquiry learning model to exercise students critical thinking skills on reaction rate material - R. Ayu Sofiah Wilatika; Bertha Yonata (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
The goal of this study is to explain how the inquiry-based learning model is put into practice, student activities during learning, critical thinking skills learning results, and learning outcomes in knowledge. Students in class XIÃÂ-IPA 5 SMA Negeri 1 Menganti Gresik Jawa Timur were the study's subjects. This type of study uses a pre-experimental design with a One-Group Pretest-Posttest Design. Data analysis using percentage techniques, normality tests, N-Gain, and paired sample t-test showed a sig value ofÃÂ 0.000. (1) The quality of the guided inquiry learning model implementation was 93% in Phase 1.94% in Phase 2.93% in Phase 3.91% in Phase 4.88% in Phase 5, and 90% in Phase 6, according to the findings of this study; (2) Relevant student activities dominate irrelevant student activities; (3) The average value of N-gain on the interpretation indicator of 0.80 (high), inference of 0.84 (high), analysis of 0.74 (high), and explanation of 0.76 (high) indicates that students' critical thinking skills have improved; (4) In the area of knowledge, learning outcomes of students achieved classical completeness of 91.43%, which exceeded the Minimum Completeness Criteria.